Cognitive-behavioural therapy reduces psychological distress in younger patients with cardiac disease: a randomized trial. (18th January 2023) - Holdgaard, Annette; Eckhardt-Hansen, Christine; Lassen, Christina Funch; Kjesbu, Ingunn Eklo; Dall, Christian Have; Michaelsen, Kristine Lund; Sibilitz, Kirstine Lærum; Prescott, Eva; Rasmusen, Hanne Kruuse
Abstract: Aims: To test whether usual outpatient cardiac rehabilitation (CR) supplemented by a cognitive-behavioural therapy (CBT) intervention may reduce anxiety and depression compared with usual CR. Methods and results: In this multicentre randomized controlled trial, 147 cardiac patients (67% men, mean age 54 years, 92% with coronary artery disease) with psychological distress defined as a hospital anxiety and depression scale (HADS) anxiety or depression score ≥8 were randomized to five sessions of group CBT plus usual CR (intervention, n = 74) or CR alone (control, n = 73). Patients with severe distress or a psychiatric diagnosis were excluded. The intervention was delivered by cardiac nurses with CBT training and supervised by a psychologist. A reference, non-randomized group (background, n = 41) of consecutive patients without psychological distress receiving usual CR was included to explore the effect of time on HADS score. The primary outcome, total HADS score after 3 months, improved more in the intervention than in the control group [the mean total HADS score improved by 8.0 (standard deviation 5.6) vs. 4.1 (standard deviation 7.8), P < 0.001]. Significant between-group differences were maintained after 6 months. Compared with the control group, the intervention group also had greater adherence to CR ( P = 0.003), more improvement in the heart-related quality of life (HeartQoL) at 6 months ( P < 0.01), and a significant reduction in cardiac readmissions at 12 months ( P < 0.01). The background group had no significant change in HADS score over time. Conclusion: Brief CBT provided by cardiac nurses in relation to CR reduced anxiety and depression scores, improved HeartQoL and adherence to CR, and reduced cardiovascular readmissions. The programme is simple and may be implemented by CR nurses. Structured Graphical Abstract: Structured Graphical Abstract Graphical summary of the method and main findings of the present study. HADS, hospital anxiety and depression scale; HeartQoL, heart-related quality of life.